2013
DOI: 10.1021/ic401220x
|View full text |Cite
|
Sign up to set email alerts
|

New Uses for Old Drugs: Attempts to Convert Quinolone Antibacterials into Potential Anticancer Agents Containing Ruthenium

Abstract: Continuing the study of the physicochemical and biological properties of ruthenium-quinolone adducts, four novel complexes with the general formula [Ru([9]aneS3)(dmso-κS)(quinolonato-κ(2)O,O)](PF6), containing the quinolones levofloxacin (1), nalidixic acid (2), oxolinic acid (3), and cinoxacin (4), were prepared and characterized in solid state as well as in solution. Contrary to their organoruthenium analogues, these complexes are generally relatively stable in aqueous solution as substitution of the dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 73 publications
7
83
1
Order By: Relevance
“…42 Ligand-exchange reaction on the ruthenium ion caused by DMSO tends to reach an equilibrium, in which, according to Turel, 10−50% of the ligand may remain free. 12 However, in aqueous solutions, exchange of the anionic (halogenide) ligands is considered to be a part of the complex activation. The newly formed complex has enhanced reactivity with nucleophilic targets in the cells.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Ligand-exchange reaction on the ruthenium ion caused by DMSO tends to reach an equilibrium, in which, according to Turel, 10−50% of the ligand may remain free. 12 However, in aqueous solutions, exchange of the anionic (halogenide) ligands is considered to be a part of the complex activation. The newly formed complex has enhanced reactivity with nucleophilic targets in the cells.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…10,11 Recent studies on ruthenium complexes with the quinolone showed an increased toxicity against selected cancer cell lines. 12,13 The synthesis of two new ruthenium(II)-cymene complexes has been reported here along with their cytotoxic activities against five human neoplastic cell lines. One complex was prepared with a new ligand, 1-(7-chloroquinolin-4-yl)thiourea (L1), and the other with 3-(4,5-dihydro-1H-imidazol-2-yl)-pyridine hydrochloride (L2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…This strategy raises the interesting question of how metal binding will modulate the biological activity of the drug and if synergistic effects can be achieved this way. 20,21 Particularly promising in this context are azole-based drugs, which have been explored in the context of antifungal chemotherapy for a number of decades. 22−24 Due to the presence of free nitrogen donor centers, these compounds can easily be coodinated to a wide range of metal-coligand fragments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…KP1019 is a substance that has a potential to be used against many tumours that are resistant to cisplatin [11]. Several other ruthenium complexes were prepared and tested for biological activity and our focus in last years were ruthenium complexes of antibacterial agents quinolones [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%